Log reduction of leukemic cells and minimal residual disease by flow cytometry represent effective predictors of clinical outcome in elderly patients with acute myeloid leukemia. Issue 1 (13th May 2021) - Rossi, Giovanni; Giambra, Vincenzo; de Waure, Chiara; Giacchetta, Irene; Minervini, Maria Marta; Abbenante, Maria Chiara; Spadano, Raffaele; La Torre, Antonella; Scalzulli, Potito Rosario; Cascavilla, Nicola
Abstract: Background: Nowadays minimal residual disease (MRD) and log‐reduction of leukemic cells are poorly investigated in elderly patients with acute myeloid leukemia (AML) treated with hypometilating agents (HMAs). Studies focusing on MRD in elderly AML patients who received HMAs are scant and devoid of rigorous criteria for both enrollment and monitoring. Log‐reduction has never been investigated in these patients. Thus, the purpose of our study was to compare the prognostic impact of MRD and log‐reduction of leukemic cells at the optimal time of assessment in older AML patients. Methods: Elderly patients who completed at least six cycles of HMAs and showed suitable leukemia‐associated immunophenotypes (LAIPs) for the MRD and log‐reduction assessment by flow cytometry were enrolled in the study. Results: After comparing the times of assessment C4 (4‐cycles) and C6 (6‐cycles), C6 has been chosen as optimal. Patients who achieved MRD negativity or 2‐log‐reduction of leukemic cells at C6 had a significantly longer DFS. Particularly, results of 2‐log‐reduction were confirmed a multivariate analysis. Patients with MRD negativity or 2‐log reduction of leukemic cells showed an improvement of their OS, although not significantly. Conclusions: Our data confirmed the predictive role of MRD and 2‐log reduction also in older AML patients treated with HMAs.